2022
DOI: 10.1007/s10648-022-09672-7
|View full text |Cite
|
Sign up to set email alerts
|

How Strongly Is Personality Associated With Burnout Among Teachers? A Meta-analysis

Abstract: Teachers’ burnout has severe consequences for themselves and their students. The identification of factors related to burnout can provide valuable information about the relevance of interindividual differences. Beyond work-related factors, burnout is assumed to be affected by individuals’ personality traits, and several empirical studies already exist that have investigated this association in teachers. However, a comprehensive meta-analytical examination is missing so far. The current meta-analysis, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 80 publications
1
19
0
1
Order By: Relevance
“…Furthermore, our results suggest that teachers’ personality matters: Teachers with higher openness and lower extraversion were better able to adapt than teachers with lower openness and higher extraversion. The impact of teachers’ personality for teaching success and well-being in normal times is a vital area of research (e.g., Roloff et al, 2022). To date, however, little has been known about its importance for teachers’ successful adaptation to the challenges of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our results suggest that teachers’ personality matters: Teachers with higher openness and lower extraversion were better able to adapt than teachers with lower openness and higher extraversion. The impact of teachers’ personality for teaching success and well-being in normal times is a vital area of research (e.g., Roloff et al, 2022). To date, however, little has been known about its importance for teachers’ successful adaptation to the challenges of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found a buffering effect of openness to experiences. In normal prepandemic times, high openness is related to lower levels of well-being (Klusmann et al, 2012) or not associated with it (Roloff et al, 2022). However, our results suggest that openness is a significant resource when adapting to new and unpredictable challenges such as teaching under pandemic constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Cadets experiencing emotional distress, perhaps from academic work overload, role conflict and other stressors in the police academy, are likely to be high on burnout. In addition, different negative emotional dimensions such as psychological strains (Salvagion et al, 2017), emotional labour (Kwak et al, 2018;Schaible and Gecas, 2010) and neuroticism (Bianchi, 2018;Roloff et al, 2022;Yusoff et al, 2021) have been found to positively predict burnout. On this premise, I hypothesize: H6: Cadets high in academic-emotional distress will be high in burnout.…”
Section: Academic Work Overload Academic-to-police Role Conflict Emot...mentioning
confidence: 99%
“…Moreover, the big-five personality dimensions of extraversion, openness, agreeableness, and conscientiousness (Swider and Zimmerman, 2010) as well as emotional intelligence (Mérida-López and Extremera, 2017), were found to be protective factors related to burnout. On the other hand, perfectionistic concerns (Hill and Curran, 2015), early maladaptive schemas (Simpson et al, 2019), high novelty seeking (Khosravi et al, 2020), and the big-five dimension neuroticism (Swider and Zimmerman, 2010;Roloff et al, 2022) were identified as vulnerability factors in relation to burnout.…”
Section: Introductionmentioning
confidence: 99%